The Effect of Therapeutic Meibomian Glands Expression on Evaporative Dry Eye: A Prospective Randomized Controlled Trial. (1st February 2021) - Kaiserman, Igor; Rabina, Gilad; Mimouni, Michael; Sadi Optom, Naava. B.; Duvdevan, Nitsan; Levartovsky, Shmuel; Ben David, David
ABSTRACT: Purpose: To determine the clinical benefits of Meibomian gland expression therapy for the treatment of dry-eye disease caused by Meibomian gland dysfunction (MGD). Methods: In a prospective randomized controlled double-masked trial, 87 eyes of 44 patients with MGD and dry-eye symptoms were enrolled. Patients were randomly assigned into two groups; a study group that received therapeutic Meibomian gland expression once every month, and a control group that received sham treatment. All patients received treatment with artificial tears. Results: One week after the first treatment, the Ocular Surface Disease Index (OSDI) score improved significantly in the study group (mean change −18.5 ± 21.2, p = .01) but not in the control group (−3.8 ± 15.8, p = .16); after 1 month, both groups improved significantly (−20.5 ± 19 p = .001 in the study group and −6.5 ± 11, p = .016 in the control group). The improvement continued at 2 months in the study group (−28.4 ± 26.1, P < .0001) and in the control group (−9.6 ± 9.9, p = .007). The blepharitis questionnaire score improved in the study group compared to controls after 1 week (−9.95 ± 12.52 versus −1.77 ± 9.1, p = .03) 1 month (−11.5 ± 10.9 versus −1.1 ± 9.4, p = .02) and 2 months (−16.5 ± 8.0 versus −8.8 ± 11.7, p = .02). Burning sensation was significantly reduced only in the study group. Mean change after 2-month treatment was −2.00 ± 1.2583 ( p < .0001) vs −0.67 ± 1.44 ( p = .08). The trend was similar in Eyelid scales. Conjunctival hyperemia improved only in the study group 1 week after the treatment (−0.12 ± 0.32 p = .03). Conclusion: Therapeutic Meibomian gland expression improves dry-eye symptoms in subjects with MGD, compared to conventional treatment with artificial tears.